Pelatihan dan Implementasi Penyusunan Laporan Keuangan pada Koperasi Simpan Pinjam Sumekar Pathok Yogyakarta - Miftahurrohman Miftahurrohman; Sri Wahyuning; Kasih Purwantini; Heny Heny (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Lack of mastery and understanding of cooperative accounting is the root of the problems faced by Sumekar savings and loan cooperatives, these problems are the background to which training activities are carried out. The aim of this activity is to increase understanding and knowledge about cooperative accounting for cooperative administrators and members both conceptually and technically. The activity partner is the Sumekar Sanggrahan Pathuk Yogyakarta Savings and Loans Cooperative. The method used in this training activity is lecture and discussion. Implementation of this training activity provides benefits in increasing understanding and knowledge of financial accounting conceptually and technically and can then be implemented to support cooperative business activities. The evaluation results of training activities show that the level of absorption and understanding of the material presented is very good, this is evident from the results of the average evaluation score for training participants of 85.58. Considering the great benefits provided by training activities, similar training can be carried out in organizations or community groups such as MSMEs so that it can contribute to increasing their knowledge in managing finances more effectively and efficiently..